ANALISIS PERBEDAAN BESARAN PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA SEBELUM DAN SESUDAH PEMENUHAN GOOD CORPORATE GOVERNANCE BERDASARKAN KEPUTUSAN-399/BEJ/07-2001 - Abubakar Arif; Tuntun Asi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2009)
The research aims distinguish differentiation profitability (gross profit margin, operating profit margin, net profit margin, earnings per share, return on total assets ,dan return on total equity) of manufacturing company listed in Indonesia Stock Exchange befor and after implementing good corporate governance. One hundred and fourty for manufacturing registered companies in Indonesia Stock Exchange were used as research sample. These samples were selected by using purposive sampling method using critrerias that determined by researcher and Bapepam decision no399/BEJ/07-2001.The result of the research, there is significant differentiation of profitability befor and after implmenting good corporate governance.